2021
DOI: 10.3897/pls2020581/04
|View full text |Cite
|
Sign up to set email alerts
|

Last tesserae of a fading mosaic: floristic census and forest vegetation survey at Parche di Bilello (south-western Sicily, Italy), a site needing urgent protection measures

Abstract: This paper illustrates the botanic heritage of Parche di Bilello, a site located in the municipality of Castelvetrano. The study area hosts several woodland fragments dominated by Olea europaea var. sylvestris, Quercus suber and Quercus ilex, respectively. According to historical data, these nuclei represent the last remnants of an open forestland which covered a much wider coastal area between Mazara del Vallo and Sciacca until the end of Middle Age. Phytosociological relevés were focused on these forest nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…In fact, two of them (metamorphites, quartzarenites, etc.). This led to a subsequent update of the distribution of the habitat 9320 in Sicily Rivieccio et al 2020;Bazan et al 2021), in the same way as other scrub formations reported for the western part of Sicily and the small islands (e.g., Caldarella et al 2011;Gianguzzi et al 2011Gianguzzi et al , 2012Gianguzzi et al , 2014aGianguzzi et al , 2014bGianguzzi et al , 2015Gianguzzi et al , 2018Gianguzzi and La Mantia 2009; La Rosa et al 2021;Romano et al 2006;etc. ), leading to an implementation of the 4th Italian Report of Habitats.…”
Section: Notesmentioning
confidence: 73%
“…In fact, two of them (metamorphites, quartzarenites, etc.). This led to a subsequent update of the distribution of the habitat 9320 in Sicily Rivieccio et al 2020;Bazan et al 2021), in the same way as other scrub formations reported for the western part of Sicily and the small islands (e.g., Caldarella et al 2011;Gianguzzi et al 2011Gianguzzi et al , 2012Gianguzzi et al , 2014aGianguzzi et al , 2014bGianguzzi et al , 2015Gianguzzi et al , 2018Gianguzzi and La Mantia 2009; La Rosa et al 2021;Romano et al 2006;etc. ), leading to an implementation of the 4th Italian Report of Habitats.…”
Section: Notesmentioning
confidence: 73%